Construction of a plant expression vector containing the replication initiation protein (REP) gene of the Abaca bunchy top virus (ABTV) - Lipio, Patrick Louie G.; Roa, Marylette; Quirante, Kristine Ace F.; Polido, Mary Ann Robelle L.; Aquino, Vermando M. (2011)
The abaca industry in the Philippines produces an average of 68,862 metric tons per year of fiber utilized on many industries generating n income of USD 80.8M on exports alone. However, viral diseases like Abaca bunchy top virus (ABTV) cause damaging effects to the plant. A strategy to control ABTV is through pathogen derived resistance (PDR) wherein a virus component is introduced to the plant and its expression and mediate resistance to the virus. The replication initiation protein (Rep) gene, an ABTV DNA virus component is a possible candidate for PDR. For this study, the Rep gene was isolated and cloned to a plant expression vector. Primers were designed to target the Rep gene and appended with restriction endonuclease sites BglII and BsteII for subsequent cloning. Amplification using the designed Rep primers and genomic DNA from ABTV infected abaca plants from Leyte yielded an approximately 900bp product. This was further subcloned to pCR2.1® TOPO® vector for sequencing. Sequencing results showed 99% similarity to the Banana bunchy top virus (BBTV) Rep gene. The pCR2.1® TOPO®-Rep construct was digested with BglII and BstEII as well as the plant expression vector pCAMBIA1302. The lligated pCAMBIA1302-Rep gene construct was transformed in DH5á cells for propagation and screening. Screening using CaMV35S and NosTer pCAMBIA vector specific primers showed an approximately 1100bp product. Further sequencing is necessary to confirm if the Rep gene is inserted to pCAMBIA1302. This construct would be delivered to abaca plant cells for assessment of its expression nd at most conferring ABTV resistance to the plant.
Keywords: Abaca diseases and pests; Plant diseases; Abaca